Effects of medicinal plants mixture on growth performance, nutrient digestibility, blood profiles, and fecal microbiota in growing pigs - Nguyen Cong Oanh; Truong Quang Lam; Nguyen Dinh Tien; Jean-Luc Hornick; Vu Dinh Ton (Veterinary World, 2021)
Background and Aim: Alternative natural materials to antibiotics for improving digestive health and growth performance are needed due to strengthening regulations related to the use of antibiotic growth promoters. The study aimed to evaluate the effects of medicinal plants mixture (60% Bidens pilosa L., 15% Urena lobata L., 15% Pseuderanthemum palatiferum, 5% Ramulus cinnamomi, and 5% Star anise) as alternative growth promotors on animal health, nutrient digestibility, blood parameters, and growth performance of growing pigs.